2016
DOI: 10.1155/2016/8797691
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach for Enterocutaneous Fistula Treatment with the Use of Viable Cryopreserved Placental Membrane

Abstract: Enterocutaneous fistulas (ECF) are a difficult and costly surgical complication to manage. The standard treatment of nil per os (NPO) and total paraenteral nutrition (TPN) is not well tolerated by patients. TPN is also known for complications associated with long term central venous catheterization and for high cost of prolonged hospital stay. We present two low output ECF cases successfully treated with viable cryopreserved placental membrane (vCPM) placed into the fistula tracts. One patient is a 59-year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…A recent surgical report by Nichols & Overly presented successful treatment of refractory low-output enterocutaneous fistulas without recurrence using a single application of vCPM. 39 In a prospective multicenter clinical trial, vCPM showed clinical benefits in the management of complex diabetic foot ulcers with exposed bone and tendon. 40 Results of this trial were confirmed by a head-to-toe complex wound case series.…”
Section: Discussionmentioning
confidence: 99%
“…A recent surgical report by Nichols & Overly presented successful treatment of refractory low-output enterocutaneous fistulas without recurrence using a single application of vCPM. 39 In a prospective multicenter clinical trial, vCPM showed clinical benefits in the management of complex diabetic foot ulcers with exposed bone and tendon. 40 Results of this trial were confirmed by a head-to-toe complex wound case series.…”
Section: Discussionmentioning
confidence: 99%
“…The main goal of all these different techniques is the isolation of the fistula opening from the open abdominal wound. In a clean wound without faecal contamination surrounding the EAF, there is an approximately 50% chance of spontaneous closure of the EAF, which is comparable with the few reported long‐term successful endoscopic closure rates . On the other hand, the use of NPWT with fistula isolation for EAF management has the advantage of combined treatment of the wound and the EAF …”
Section: Discussionmentioning
confidence: 60%
“…Besides SFA and SLS, a variety of other techniques and tools are described for the successful fistula isolation of EAF from the rest of the wound using the NPWT in an open abdomen situation . Recently, new endoscopic treatment options for the management of EAF have been described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations